(untitled) (Foro de Educacion, 2019)
This paper explores my on-going collaborative research journey that began in 2009 with a critical ethnographic investigation into the ways one early years school in Bristol was working to advance a pedagogy of respect that drew on the multilingual and multiliterate out of school practices of children and their parents in order to open possibilities for in-school learning. The project was framed within a critical ethnographic approach that is underpinned by a philosophy of democratic and collaborative ways of working within the field; acknowledging identities, positionalities and relations of power as constructed within and across institutional settings. In this paper, I present the collaborative learning trajectories and relationships between myself, as researcher, and Lara, the Head Teacher, a key participant within this project. I situate this within a critical reading of researcher identities, collaboration and research-community partnerships within a scholarship that draws on arguments for the democratizing of knowledge production, the re-evaluation and transformation of field relationships through reflexive practice (Byrd-Clark & Dervin, 2014; Facer & Enright, 2016; Giampapa, 2011) and the intellectual and emotional commitment involved in shaping them. What evolved through this unfinished critical ethnographic journey is an understanding of the underlying «practical, personal and symbolic» reasons (Facer & Enright, 2016, p. 59) for field relationships as a starting point in order to build deeper forms of engagement. These deeper forms of engagement generate different ways of knowing that are co-created, ethically grounded, socially responsible and action oriented (Campbell & Lassiter, 2010). I stress the transformative power of these field conversations that were able to evolve and shape new ways of understanding as a result of the longevity of being in the field and working beyond it.